Tarjamah Mūjazah li al-Shaykh Muḥammad ibn ʻUmar al-Nawawī - Hasan Basri Salim (Al-Zahra : Journal for Islamic and Arabic Studies, 2007)
Muhammad ibn Umar an-Nawawi better known by the name of Nawawi Al-Bantani. He was known as an expert badis, lafsir, filch, and Sufis. His works have been studied in various universities around the world. This paper describes the biography, works, and his wanderings in the study.